Answer:
The common difference (or common ratio) = 0.75
Step-by-step explanation:
i) let the first term be
= 80
ii) let the second term be
=
. r = 80 × r = 60 ∴ r =
= 0.75
iii) let the third term be
=
. r = 60 × r = 45 ∴ r =
= 0.75
iv) let the fourth term be
=
. r = 45 × r = 33.75 ∴ r =
= 0.75
Therefore we can see that the series of numbers are part of a geometric progression and the first term is 80 and the common ratio = 0.75.
Step-by-step explanation:
(f+g)(x) ➡ f(x) + g(x) ➡ 6x^2 + 2x -7 + 4x - 3 =6x^2 + 6x - 10
(f-g)(x) ➡ f(x) - g(x) ➡ 6x^2 + 2x - 7 -4x + 3 = 6x^2 -2x -4
Answer:
does anyone know the answer????????
Step-by-step explanation:
aaaaaaaaahhhhhh pleaseeeeeeeeee fasssssssstttttttttttttttttttt someeeoneeeeeeeeeeeeeeeee
Answer:
379.94
Explanation :
check out my attached work
Hope it helps, let me know if you have any questions !
Have a nice rest of your day :)
Answer:
i). x³ + 9x² + yz - 15
ii). -21m³np - 8p⁵q + mnp + 4mn + 100
Step-by-step explanation:
Question (38)
i). Two expressions are -5x² - 4yz + 15 and x³+ 4x²- 3yz
By subtracting expression (1) from expression (2) we can the expression by addition which we can get expression (1).
(x³+ 4x²- 3yz) - (-5x² - 4yz + 15) = x³ + 4x² - 3yz + 5x² + 4yz - 15
= x³ + 9x² + yz - 15
ii). -15m³np + 2p⁵q - 6m³pn + mnp + 4mn - 10qp⁵+ 100
= (-15m³np - 6m³np) + (2p⁵q - 10qp⁵) + mnp + 4mn + 100
= -21m³np - 8p⁵q + mnp + 4mn + 100